Prevalence of self‐reported chronic pain among adolescents: Evidence from 42 countries and regions. (3rd September 2018) - Gobina, Inese; Villberg, Jari; Välimaa, Raili; Tynjälä, Jorma; Whitehead, Ross; Cosma, Alina; Brooks, Fiona; Cavallo, Franco; Ng, Kwok; de Matos, Margarida Gaspar; Villerusa, Anita
Abstract: Background: Reports of the overall chronic pain prevalence and its associated demographic characteristics among adolescents vary greatly across existing studies. Using internationally comparable data, this study investigates age, sex and country‐level effects in the prevalence of chronic single‐site and multi‐site pain among adolescents during the last six months preceding the survey. Methods: Data ( n  = 214, 283) from the 2013/2014 Health Behaviour in School‐aged Children (HBSC) study were used including nationally representative samples of 11‐, 13‐ and 15‐year‐olds from general schools in 42 participating countries. Multilevel logistic regression analyses were used. Results: The overall proportion of adolescents reporting chronic weekly pain during the last six months was high (44.2%). On average, in comparison with different specific localized types of single‐site pain, the prevalence of multi‐site pain was more common varying from 13.2% in Armenia to 33.8% in Israel. Adolescent age and sex were strong predictors for reporting pain, but significantly different demographic patterns were found in the cross‐country analyses. The most consistent findings indicate that multi‐site pain was more prevalent among girls across all countries and that the prevalence increased with age. Conclusions: Internationally comparable data suggest that self‐reported chronic pain among adolescents is highly prevalent, but different age and sex patterns across countries exist. Adolescents with chronic pain are not a homogenous group. Chronic pain co‐occurrence and differences in chronic pain characteristics should be addressed in both clinical and public health practice for effective adolescent chronic pain management and prevention. Significance: Chronic pain co‐occurrence is common during adolescence across countries, the prevalence being among girls and in older age groups. Significant cross‐country variations in the chronic pain prevalence and chronic pain patterns among adolescents exist. Significant country differences emerge for specific chronic pain patterns in association with adolescent demographics.